Legal Responsibility of Digital Platform Companies for Protecting Shareholder Losses in The Era - Siregar, Boni; Sihotang, Lesson; Nababan, Roida (Journal of Law and Social Politics, 2025)
The era of e-commerce has presented a great opportunity for digital platform companies to expand financial services, including stock investment. However, the complexity of technology and business models often poses risks for investors. This article aims to analyze the legal responsibilities of digital platform companies in protecting stock investors in the era of e-commerce. This research uses a normative method with a legislative approach and case studies. The results show that the protection of stock investors is highly dependent on adaptive regulation and the implementation of strict legal responsibilities by digital platforms. It is recommended that companies improve transparency, technology security, and user education to strengthen investor confidence. What is the legal responsibility of digital platform companies in protecting stock investors from legal and technological risks in the e-commerce era? And what are the regulatory efforts in Indonesia able to ensure legal protection for stock investors who use digital platforms, and what steps need to be taken to overcome the regulatory loophole?